(untitled) (Journal of the College of Education for Women, 2019)
Domesticated translation has been for a long time the norm in cultural communication between nations all over the world. The texts are translated mainly into English (being the dominant language) in terms dictated principally by the requirements of the target language (English). The claim has been that fluency, readability, and immediate intelligibility can be guaranteed as far as the reader of the target language is concerned (English). The foreignness of the text (of the culture which produced it) would be not preserved. Not only this. Being the language of predominant cultures, English has become number one among languages into which texts are translated. The imbalance has been noticeable between the volumes of works translated from and into English English. The result is inequality in cultural exchanges and communication. What is rather alarming for researchers in the field of Translation Studies, Translation theorists and scholars in language and linguistics is a drift in the direction of a monolingualism and monoculturalism. This is why they have been working to set the balance right by first of all making the role of the translator visible. This is what Venuti makes it clear in his book ‘The Translator’s Invisibility,” The motive of this book is to make the translator more visible so as to resist and change the conditions under which translation is theorized and practiced.”(1995: 17) Foreignized translation as opposed to domesticated translation is highly advocated by Venuti and other scholars to achieve the change aspired. Consequently, the culture of the other can be preserved and better communicated with.